Methods in behavioral research - Cozby, Paul C. (McGraw-Hill Higher Education, 2007)
"Methods in Behavioral Research" is a concise introduction to research methods for psychology and behavioral science courses. It has been the best selling title in this course for at least fifteen years, and is considered by many to be the most student-friendly text for research methods - the one that students will read